Fresno County Bar Association Luncheon with Presiding Judge Stephen Henry - Watkins, Howard::::::::: (1988)
Fresno County Bar Association President Herbert Levy welcoming everyone to the Bar luncheon. Hon. Stephen Henry and Samuel Palmer III seated.